Organizational Effectiveness as The New ‘Babel of Tongues’ Of Management Science - Witold KOWAL (Communications of International Proceedings, 2024)
One of the most notable properties of the modern scientific output – particularly in the realm of social sciences – is the cumulative character of knowledge. This poses a serious challenge for science, which must deal with an apparent ‘oversupply’ of knowledge, taking the form of theories. The multitude of scientific representations presents science with the problem of their effectiveness, related to their cognitive function, and above all the ability to predict. The aim of the article is to present how contextuality influenced the development of organizational effectiveness theories and how this knowledge developed cumulatively. This paper is based on review and critique of extant literature on organizational effectiveness. The main finding of the conducted studies is that, from the point of view of explanatory methods, contextual approach dominates in the interpretation of organizational effectiveness, and the category of organizational effectiveness as a theory has become very complex. Its universality has been replaced by numerous interpretive contexts. The modern interpretation of organizational effectiveness resembles the "Tower of Babel", which reflects knowledge developed cumulatively.
Keywords: methods of scientific explanation; contextuality; organizational effectiveness